sRAGE, Inflammation, and Risk of Atrial Fibrillation: Results from the Atherosclerosis Risk in Communities (ARIC) Study - Al Rifai, Mahmoud (J Diabetes Complications, 2014)
OBJECTIVE: Advanced glycation end products (AGEs) may cause inflammation by binding to their cellular receptors (RAGE). Soluble RAGE (sRAGE) acts as a decoy receptor for AGEs and may prevent inflammation. Chronic low-grade inflammation is a risk factor for cardiovascular disease, including atrial fibrillation (AF). METHODS: We studied 1,068 participants in a subsample of the Atherosclerosis Risk in Communities (ARIC) Study who had baseline measurements of sRAGE (mean age 56, 60% female, 21% black). Inflammation was assessed using measurements of high sensitivity C-reactive protein (hsCRP), fibrinogen, gamma-glutamyl transferase (GGT) and white blood cell (WBC) count. AF events were identified using ECG data, hospitalization discharge codes, and linkage to the National Death Index. RESULTS: Compared to the highest quartile (>1272.4 pg/mL), the lowest quartile of sRAGE (<714 pg/mL) was associated with higher baseline levels of inflammation (hsCRP ≥3 mg/L: OR=2.21 [95%CI 1.41–3.49], fibrinogen ≥400 mg/dL: OR=4.31 [95%CI 1.50–12.41], GGT ≥36 U/L in women and ≥61 U/L in men: OR= 5.22 [95%CI 2.66–10.22], WBC >6.2×10(9)/L: OR=2.38 [95%CI 1.52–3.72]). sRAGE was not prospectively associated with 6-year change in inflammatory markers (hsCRP or GGT). There was no significant association of sRAGE and risk of AF (HR 1.49 [95% CI: 0.80–2.78] for the 1(st) vs 4(th) quartile of sRAGE). CONCLUSIONS: sRAGE was strongly inversely associated with markers of inflammation at baseline, but not prospectively. sRAGE was not significantly associated with incident AF. This supports a role for sRAGE in attenuating current inflammation, but it remains unclear whether sRAGE plays a role in the development of AF.